Studies of pure homogeneous deformations in unfilled natural and butyl rubbers - Hall, M. M. (Cranfield University, 1968)
Observed deviations from the kinetic theory of rubberlike elasticity have been reviewed, and particular attention focussed upon the Mooney parameter C2. Stress measurements have been made upon thin rubber sheets in a state of pure homogeneous biaxial strain, and the stress relaxation behaviours of a natural rubber and a butyl rubber are reported … [cont.].